Survei Manajemen Pengelolaan Olahraga Rekreasi River Tubing Desa Wisata Pandansari Kecamatan Warungasem Kabupaten Batang Tahun 2021 - Utami, Anisa Nur Puspa; Irsyada, Roas (Universitas Negeri Semarang, 2023)
The purpose of this research is to know the management process covers planning, organizing, directing, and supervision vehicle sport recreational River Tubing Village Tour Pandansari Regency of Batang In 2021. Focus problem in study this : 1) How planning vehicle sport recreation Pandansari River Tubing Batang Regency? 2) How organizing vehicle sport recreation Pandansari River Tubing Batang Regency? 3) How actuating in implementation of the program on the vehicle sport recreation Pandansari River Tubing Batang Regency? 4) How controlling program on the rides sport recreation Pandansari River Tubing Batang Regency?. Research methods this descriptive qualitative with method collection of observational data, interviews, and documentation. Target study this are managers, coordinators treasurer, clerk, as well visitor. Results research : 1) The planning process is carried out by Pandansari river tubing management already walk in accordance with function management. 2) Organizing is done by Pandansari river tubing management already walk with doing the basics a good organisation. 3) The actuating process carried out Pandansari river tubing management conducted by a general manager. Every briefing conducted in meeting coordination. 4) Controlling carried out by Pandansari river tubing management already walk in accordance with function.